Generalized multivariate regression estimators for multi-phase sampling using multi-auxiliary variables - Ahmad, Z.; Hussin, A.G.; Hanif, M. (ISOSS Publ, 2010)
In this paper we propose a number of generalized multivariate regression estimators for two-phase and multi-phase sampling in the presence of multi-auxiliary variables for estimating population mean for a single variable and a vector of variables of interest(s). The expressions for mean square errors have also been derived. The suggested estimators have been theoretically compared and an empirical study has also been conducted.